Digital forensic intelligence for illicit drug analysis in forensic investigations - Mayssa Hachem; Rabeb Mizouni; Ibtesam Mohammed Alawadhi; Mohamad J. Altamimi (iScience, 2023)
Summary: In forensic investigations, forensic intelligence is required for illicit drug profiling in order to allow police officers and law enforcements to recognize crime developments and adjust their actions. In the present paper, we propose a novel framework for Digital Forensic Drug Intelligence (DFDI) by fusing digital forensic and drug profiling data through intelligent cycles, where a targeted and iterative collection of evidence from diverse sources is a core step in the process of drug profiling. Drug profiling data combined with digital data from seized devices collected, examined, and analyzed will allow authorities to generate valuable information about illicit drug trafficking routes and manufacturing. Such data can be stored in seized illicit drug databases to build in an intelligent way, all findings, hypotheses and recommendations, allowing law enforcement to make decisions. Our framework will potentially provide a better understanding of profiling, trafficking and distribution of illicit drugs.